IMPROVEMENT OF SUPERVISORY CONTROL OF TRAIN MOVEMENT BY MEANS OF INTRODUCTION OF OPERATIONAL ZONES - Nesterenko, H. I.; Bech, P. V.; Muzykin, M. I.; Avramenko, S. I. (Science and Transport Progress, 2019)
Purpose. The work is aimed to investigate the feasibility of transferring automatic control to low-density stations of the sections (according to the principle of supervisory control of trainline) to the operators at principal stations. Methodology. The article analyzes the work of heavy traffic sections of the Ukrainian Railways JSC. It was found out that the information workload of dispatchers who control the train movement at the sections of the main course, constantly exceeds the permissible level. The possibility of using the technology of supervisory control of train movement by the introduction of operational zones has been investigated. Findings. The authors found out that the capacity of receiving and departure tracks at the stations of the sections is extremely limited. The occupancy of run-around tracks by the out-of-work trains hinders any regulatory measures at the sections. Trains pass one after another without giving priority, that is, they pass through the section in the order in which they entered it. Due to the limited number of tracks at the pre-section intermediate station, freight trains are placed for run-around by the passenger ones at the distant approaches. This leads to a loss of service speed and reduces the level of utilization of the sections` working capacity. The introduction of operational zones will significantly reduce information flows and facilitate the work of the train dispatchers, create the necessary conditions for creative decision-making on the inter-sectional regulation, and will contribute to increase in the service speed of trains. Originality. The article developed a new technology to improve the management of train sections by dividing them into operational zones. In each zone, consisting of two or three run-arounds, the duty officer of the principal station, performing in this case the functions of the train dispatcher, can control the train movement. Practical value. It has been proposed to put trains from technical stations that idle due to uneven movement, especially the trains from the terminal stations (division points) of the locomotive circulation sections, to reserve routes of the pre-section intermediate stations. Laying the reserve tracks and their maintenance, taking into account the periodicity of use and reduced permissible speed, can be allowed according to less tight standards for the construction of the roadbed, ballast section, sleeper density, taking into account the use of switches and decommissioned tracks.